The effectiveness of hearing conservation for offshore workers in an offshore oil and gas platform environment - Lai, Leo Ong Bah (2001)
Noise has long been recognized as one of the most prevalent workplace hazards. Noise induced hearing loss progression (NIHL), however, is insidious, in that it developed over a period of time, and the impairment can reach the handicapping stage before an individual is aware of what has happened. Once the damage is done, it is irrecoverable and not curable. All of the producing oil and gas fields in Malaysia are mainly located offshore. Offshore platforms and facilities are generally very costly to install and to maintain. Additional costs are incurred by using barges and marine support vessels. Hence, the design tend to maximize the valuable space available to house all necessary equipment and machinery whereby noise generation can be significant. Staff working offshore is, therefore, exposed to such noise. The paper analyses how noise management is carried out to manage noise risks exposure to the staff working offshore working on a 2 weeks ON 2 weeks OFF work cycle and to evaluate its effectiveness using oil platform D35 complex off Miri as a case study. The methodology applied in this study was by using questionnaire and observation, which confirmed on non-compliance to the wearing of hearing protectors in high noise area, which is the main cause ofNIHL. The questionnaire survey revealed that some 12% non-compliance to the hearing conservation and as high as 22% having varying degree of potential sociocusis related noise exposure. ACT (Accident Control Technique) observations showed there were some 6% hearing protection violations in high noise level area.